Pengaruh Pemakaian Kertas Lem Perasan Sampah Ikan Terhadap Jumlah Lalat Terperangkap di TPS Terminal Baturraden Tahun 2018 - Desi Setianingsih; Djamaluddin Ramlan; Khomsatun Khomsatun (Jurnal Sehat Mandiri, 2019)
Fly is a transmitting vector of gastrointestinal disease. Indonesia is a fish-producing paradise. Garbage generated from fishery activities if not handled properly and properly can be a place to miss a fly that will cause many problems for humans. So there should be effort to control fly one of the way that is physically by using fly glue paper smeared with atraktan. The method used in this research is Pre Experiment with Static Group Comparison design. Data collection by observation and measurement. Data analysis using Rank Spearman test and Anova test. The results obtained from the measurements of the number of flies trapped for 7 days of research in 7 times the average replication on glue paper without the litter of fish waste (15 head), on glue paper with the waste of fish concentration 25% (11 fish), on paper glue with fresh fish garbage concentration 50% (9 tail), on glue paper with garbage concentration 75% (23 fish). The statistical calculation using Rank Spearman test showed significant value: 0.772> α: 0,05 and significant value: 0,081> α: 0,05. Data analysis using Anova test got result that is significant value> value α that is 0,209> 0,05. The conclusion of this research is that there is no effect of garbage volume by the number of trapped flies, no effect of flies density with number of trapped flies, and no effect of paper glue on the trash of fish trash on the number of trapped flies. Suggestions that can be given that is not to reduce the adhesiveness of the glue, the waste of fish waste is not smeared but only placed next to the glue paper.